The interplay of Turkish EFL teachers’ academic optimism, psychological well-being, and self-efficacy - Tas, Busra Turan; Tuyan, Seden Eraldemir (Asian Journal of Education and Training, 2023)
This study examined the relationships between Turkish EFL (English as a Foreign Language) teachers’ sense of self-efficacy, psychological well-being, and academic optimism. The study’s strength lies in its exploration of this question within the context of the COVID-19 pandemic, which provides a background that adds depth to the examination. Researchers collected data from 272 English as a Foreign Language (EFL) teachers during the pandemic. The study intended to identify the motivating factors underlying self-efficacy in this particular teacher set using the regression analysis perspective. The findings provided significant understanding; a strong link between self-efficacy and academic optimism was found. This shows that EFL teachers were more likely to demonstrate a better level of self-efficacy in their teaching responsibilities if they had a more positive outlook on academic outcomes. However, psychological well-being was not shown to be a significant predictor of self-efficacy. These findings shed light on a crucial aspect of classroom teacher efficiency and well-being. It shows that there is an intense desire to put teachers’ health first, particularly in challenging circumstances like the pandemic. Creating a climate of intellectual positivity should be a priority in all educational initiatives; the study can operate as guidance, directing the creation of solutions to counteract possible adverse effects on teachers’ psychological health and, consequently, their ability to teach effectively. It is concluded that this study provides insight into the complexity of teacher self-efficacy, highlighting the impact of psychological wellness, academic optimism, and crisis-related environments.